Music transformation in architectural morphology: A case study in Villa Isola Bandung - Deviana Vakhira; Siti Mutiah; Hafizhah Insani Midyanti (Universitas Pendidikan Indonesia, 2021)
Music and architecture are part of the arts, which are artistic and natural human expressions. A work of art cannot be separated from several internal or external influences. Influences that come from outside or external factors include humans, space and time. Music and architecture influence both, and the connections and aspects between the two are things that certainly have a relationship. Music and architecture have similarities in that both have rules that work in harmony—sensitivity to aesthetic principles: harmony, rhythm, balance, and emphasis. The psychological impression of colour, materials and construction also complements the realization of a complete and integral design. Music can be visualized in other forms of art, namely architecture, a field of art with a wide range of scientific fields. This article will examine the relationship between the art of music and other arts, namely architecture, including its interrelated elements and a description and analysis of the transformation of music into architectural form in Villa Isola Bandung. The discussion of this problem will use a descriptive method with a deductive approach, namely taking a case study and analyzing it in general, specifically related to theories related to music and architecture.